Effect of Pscyrotroph Bacteria on Physical and Chemical Properties of Traditional White and Ultrafilteration Cheese - EZZATI, R.; DEZYANI*, M.; ALLAH MIRZAEI†, H. (Asian Journal of Chemistry, 2009)
The dominant factor of stored raw milk in low temperature are Pscyrotroph bacteria and these bacteria as referred as to microorganisms that can survive and grow at 7 ºC or lower. Pscyrotroph bacteria is not heat resistance and pasteurization destroy them, but their proteolytic and lypolytic enzymes are heat resistance. These enzymes save their activities in pasteurization temperature and also UHT processing. In this study, effect of Pscyrotroph bacteria on physical and chemical properties on ultrafilteration and white cheese was investigated. The results showed that number of Pscyrotroph bacteria on white and ultrafilteration cheese was significant, so with increasing Pscyrotroph bacteria the dry matter per cent, per cent of fat and firmness of texture was reduced. In spite of this, moisture of curd and softness of cheese texture increased by multiplying Pscyrotroph bacteria. These changes in the ultrafilteration cheese were more than white cheese.